Percutaneous Valve-in-Valve Treatment of a (Very Old and Fluoroscopy Invisible) Degenerated Tricuspid Prosthesis Through the Right Jugular Vein Approach - Aurigemma, Cristina; Burzotta, Francesco; Corrado, Michele; Colizzi, Christian; Trani, Carlo (Frontiers in Cardiovascular Medicine, 2019)
Tricuspid valve dysfunction adversely affects prognosis and may cause severe symptoms. Among the different opportunity offered by transcatheter techniques, the valve in valve represents an emerging strategy to treat patients with degenerated surgical biological prosthesis. We describe a case report of a percutaneous valve in valve treatment of a very old and fluoroscopy invisible tricuspid degenerated bioprosthesis. In the reported case, pivotal issue for percutaneous valve in valve procedure success was the achievement of perfect alignment between transcatheter valve and degenerated bioprosthesis despite the horizontal right chamber axis and the poor valve visibility. Of note, the combination of jugular vein approach, transapical delivery system rotation, right ventricle guidewire placement and right atrium angiography made the valve in valve procedure safely.